PENGARUH MEDIA SOSIAL TWITTER @LOWKERPKU TERHADAP PEMENUHAN KEBUTUHAN INFORMASI LOWONGAN KERJA BAGI FOLLOWERS - Burhanuddin "; Rumyeni " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
As rapid technological development today, the human need for technology is growing, one of which is Internet technology, among amenity provided by the Internet is the ease of finding a job information. There were so many internet sites and social media that provide information about the job. One of the social media that provide job information is a social media twitter @LowkerPKU. Internet and social media are used to share information, job, looking for a way replace the previous job information. The follower of @LowkerPKU account can read the timeline @LowkerPKU to looking for job information. In Uses and Gratification theory of media users play an active role in selecting and using media. Media users are trying to find the best source in an attempt to meet their needs. The purpose of this study is to determine, whether there is an influence of social media twitter @LowkerPKU towards fulfillment of job information for followers.The method used in this study is a quantitative method of explanation. Data collection techniques in this study using a questionnaire. The number of samples for this study were 99 respondents. Sampling using random sampling techniques. To determine how much influence these two variables, the researchers used a simple linear regression analysis. Questionnaire for data processing, carried out using the program Statistics Product And Service Solutions (SPSS) version of Windows 17.Results of research on the influence of social media twitter @LowkerPKU towards fulfillment of job information for followers regression coefficient values obtained in this study is Y = 0.884 + 0.733 X with significance level 0,000 that smaller than α = 0.05. This means that there is the influence of social media twitter @LowKerPKU towards fulfillment of job information for followers of 46.5% and in the category of influential medium. The percentages indicate that the job information needs can be fulfilled respondents. Thus H0 is rejected and Ha accepted.Keywords : Media Social, Twitter, Infromation Needed, Job Vacancy